Peran Brain Stimulation TMS Pada Prajurit Penderita Depresi Yang Penugasan di Kapal Perang - I KETUT TIRKA NANDAKA (HANG TUAH MEDICAL JOURNAL, 2021)
Abstract Military personnel have a high risk of suffering from depression due to the nature of their work and training, separation from family, carrying out military missions, changing tasks, assignments in narrow places (warships) and being exposed to dangerous events and equipment. In a study by Al-Amri et al., in Saudi Arabia by taking 357 random samples, it was found that the prevalence of depression was 17.1% in an area of ​​military operations in the Middle East. PDSKJI (2017) reports that 3.7% of the population in Indonesia suffers from depressive disorders. This study is a case report pre and post test design as many as 4 patients of naval soldiers who have been diagnosed with major depressive disorder who will receive standard therapy in the form of antidepressants and psychotherapy. First, an assessment of the level of depression was carried out using the BDI (Beck Depression Inventory) and HDRS (Hamilton Depression Rating Scale). Standard therapy for depression was given to both groups and one group plus TMS augmentation therapy, power adjusted to RMT (resting motor threshold), TMS therapy protocol with amplitude 100% high frequency 18 Hz, 2 sec with inter-train intervals of 20 sec, 55 and 59 train for 20 minutes 5 times a week. From the results of this study, clinically all patients who received TMS augmentation showed better clinical results starting from the first week of therapy with a decrease in BDI scores of 15 points and HDRS scores of 14 points. Scores decreased by a difference of 6-8 points on the BDI scale and a difference of 5-7 on the HDRS scale in patients receiving standard therapy compared to those receiving standard therapy and TMS augmentation. Keywords : Depression – BDI / HDRS - Soldier - TMS